2019
DOI: 10.3390/pathogens8040163
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Presence of Low Pathogenic Avian Influenza A Viruses in Wild Waterfowl in 2018 in South Africa

Abstract: Avian influenza viruses are pathogens of global concern to both animal and human health. Wild birds are the natural reservoir of avian influenza viruses and facilitate virus transport over large distances. Surprisingly, limited research has been performed to determine avian influenza host species and virus dynamics in wild birds on the African continent, including South Africa. This study described the first wild bird surveillance efforts for influenza A viruses in KwaZulu-Natal Province in South Africa after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(27 reference statements)
0
6
1
Order By: Relevance
“…These intra‐African migrants walk on floating vegetation to feed on aquatic insects. The detection of AIV in this species of wild birds disagrees with the studies by Poen et al 41 who reported that no AIV was detected in the African jacana species screened in South Africa. HPAI was also detected in the cloaca and oropharyngeal samples from white stork species ( Ciconia Ciconia ).…”
Section: Discussioncontrasting
confidence: 99%
“…These intra‐African migrants walk on floating vegetation to feed on aquatic insects. The detection of AIV in this species of wild birds disagrees with the studies by Poen et al 41 who reported that no AIV was detected in the African jacana species screened in South Africa. HPAI was also detected in the cloaca and oropharyngeal samples from white stork species ( Ciconia Ciconia ).…”
Section: Discussioncontrasting
confidence: 99%
“…Every year, migratory birds that breed in the wetlands of Russia, Japan, the Korean peninsula, northeast China and east China migrate from the north to south through the coastal areas of east China in spring and autumn, which could explain the origins of class I NDVs in China and might be responsible for the complex genotype of the class I NDVs in east China (Figure 1b, Figure 2). The role of migratory birds in spreading the avian virus has also been previously demonstrated in various studies (He et al, 2020;Li, Xu, & Shaman, 2019;Poen, Fouchier, Webby, Webster, & El Zowalaty, 2019;Tolf et al, 2013;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 55%
“…This province has a rich biodiversity of wild birds, with 496 species recorded including high counts of target Afro-tropical Anseriform species such as the Cape Teal (Anas capensis), Egyptian Goose (Alopochen aegyptiacus), African Black duck (Anas sparsa), South African Shelduck (Tadorna cana), Red-billed Teal (Anas erythrorhyncha), Yellow-billed Duck (Anas undulata), Knob-billed Duck (Sarkidiornis melanotos), White-faced Whistling Duck (Dendrocygna viduata) and African Pygmy Goose (Nettapus auritus) [17]. IAVs of various subtypes were detected in some of these species and in African Sacred ibises (Threskiornis aethiopicus) in South Africa during active and passive surveillance studies [10,14,[18][19][20]. IAV dynamics are driven by the presence of immunologically naïve juvenile birds in the population that shed the highest quantities of virus, the density of host congregations, interspecies mixing and environmental conditions (especially temperature) that affect the survival of virus outside of its host [11].…”
Section: Introductionmentioning
confidence: 99%